Screening for high-purity L-lactic acid-producing thermotolerant Bacillus capable of utilizing sucrose and starch in an energy-efficient production process - Leelavatcharamas, Vichai; Moungprayoon, Ayyapruk; Sakai, Kenji; Tongpim, Saowanit (Asia-Pacific Journal of Science and Technology, 2025)
This study aimed to isolate and characterize thermotolerant Bacillus strains capable of utilizing sucrose and starch for efficient production of optically pure L-lactic acid. High-purity L-lactic acid is a valuable bio-based chemical with applications in bioplastics and other industries. Thailand’s abundant sucrose and tapioca starch byproducts present an opportunity to produce L-lactic acid from low-cost feedstocks using thermotolerant bacteria like Bacillus coagulans. Twenty-eight thermotolerant Bacillus isolates were screened for their capability to grow on glucose, sucrose, and cassava starch at 50 °C. Four strains (NF17, N24A2t, NF11, N47B2) could utilize all three carbon sources. These were further evaluated for growth, acid production profile, and L-lactic acid yield. Strain NF11, identified as B. coagulans, produced the highest L-lactic acid titter, 108 g/L from molasses, with a yield of 1.12 g/g at 50 °C under aerobic conditions. The effects of aeration, initial sugar concentration and sterilization method on L-lactic acid production were investigated using the NF11 strain. Moderate aeration at 100 rpm improved sugar utilization and lactic acid productivity over that of static conditions. An initial 100 g/L total sugar concentration from molasses was optimal. Remarkably, NF11 could produce high L-lactic acid titers without conventional heat sterilization, using only chemical sterilization with potassium metabisulfite or no pretreatment at all. This energy-efficient bioprocess employing a thermotolerant B. coagulans strain enables valorization of sugary byproducts like molasses into optically pure L-lactic acid, a valuable bio-based chemical feedstock. Eliminating energy-intensive pasteurization/sterilization offers significant cost advantages for large-scale L-lactic acid biorefineries.